Metal-based blue light material and preparation method thereof
The metal base Blu -ray material [(PMIB) (TPSP) CUBR] n used through the solution volatilizes the legal system, uses asian copper and 1,4 -double (imidazole -1 -base methyl) and other materials to form a one -dimensional chain structure to solve the solution The existing Blu -ray material has low light emitting efficiency, short service life and high material cost, and realizes high -efficiency and stable blue light launch and long service life.
Patent Information
- Application Number
- CN202411489839.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing blue light materials have low luminous efficiency, short service life and high material cost in OLED display technology, which limits the application potential of OLED technology in the fields of display and lighting.
Preparation of a metal base blue light material [(PMIB) (TPSP) CUBR] N through the solution volatilizes the legal system, and adopts sub -copper as a metal material material, combined with 1,4 -double (imidazole -1 -base methyl) as the bridge accessories, as a bridge accessories, as a bridge accessories, and Form a one -dimensional chain structure to improve the stability of light.
The efficient solid -state launch is achieved. The launch center is centered on 442nm, and the half -peak width is about 75nm. It shows relatively stable fluorescent color and zero heat ingenuity phenomenon, extending the service life and reducing the cost of material.
Smart Images

Figure CN119371441A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of crystalline functional materials, and in particular to a metal-based blue light material and a preparation method thereof. Background Art
[0002] OLED display technology occupies an important position in the modern display field with its advantages such as high contrast, bright colors, fast response and low power consumption. In OLED panels, blue light accounts for a large proportion of power consumption, so the development of efficient blue light materials is particularly critical to reducing the overall energy consumption of OLED. In addition, the stability of blue light materials is directly related to the service life of OLED devices. At present, the research and development of blue light materials lags significantly compared to red and green light materials. The main problems faced include lower luminous efficiency, shorter service life and higher material costs, which limit the application potential of OLED technology in the display and lighting fields. Therefore, in-depth research on blue light materials is of great significance to improving the performance of OLED devices. Summary of the invention
[0003] Under this background, the present invention proposes a method for preparing a metal-based blue light material, which is prepared by a simple solution volatilization method, meets the requirements of high efficiency and stability, and provides a new method for the application of blue light copper-based metal halides in the OLED field.
[0004] In order to overcome at least one of the above disadvantages of the prior art, on the one hand, the present invention provides a metal-based blue light material, wherein the metal-based blue light material is a complex, the ligand is pmib, the pmib is 1,4-bis(imidazole-1-ylmethyl), and the single crystal structure molecular formula of the metal-based blue light material is: [(pmib)(TPSP)CuBr] n The metal-based blue light material belongs to the monoclinic system, the space group is C 2 / c, and the crystal parameters are α=90°, β=116.252(3)°, γ=90°, Z=8,
[0005] Furthermore, the minimum asymmetric unit structure center of the metal-based blue light material is composed of a crystallographically independent Cu and a Br atom to form a classic [CuBr] coordination mode, which is extended outward through the connection between the Cu atom and the ligands pmib and TPSP to form a one-dimensional chain structure.
[0006] Cuprous (Cu+) as a metal has significant cost advantages compared to precious metals. Due to its abundant reserves in the earth's crust, its price is much lower than that of precious metals such as gold, silver, and platinum, which makes cuprous more economically attractive in large-scale industrial applications. Cuprous complexes are considered candidate materials for the manufacture of organic light-emitting diodes (OLEDs) due to their excellent photophysical properties. By regulating the rigidity and electronic structure of the complex structure, a zero thermal quenching effect can be achieved, thereby significantly improving the luminescence stability. These materials are simple to synthesize, low-cost, high-yield, and exhibit stable luminescence performance over a wide temperature range. Therefore, cuprous complexes are considered to be low-cost alternatives to precious metal-based luminescent materials.
[0007] A second aspect of the present invention provides a method for preparing a metal-based blue light material, the method comprising:
[0008] S1. Dissolve 2-methylimidazole and potassium hydroxide in dimethyl sulfoxide, stir to react, add α-α'-dichloro-p-xylene, and stir overnight to obtain a reaction solution;
[0009] S2. The reaction solution in the previous step was broken with distilled water, and then liquid-liquid extraction was performed with dichloromethane, and the layers were separated to obtain an organic layer, which was dried over anhydrous magnesium sulfate, filtered and concentrated;
[0010] S3. Add ether to the concentrate from the previous step, place in a refrigerator overnight, crystallize, and filter to obtain the ligand pmib;
[0011] S4. Add CuBr, pmib, TPSP, acetonitrile and dichloromethane into a beaker and stir. Filter the mixture after stirring and pour it into a clean beaker. Seal it with plastic wrap and pierce it. Volatilize it at room temperature. After the solvent evaporates, a mixture containing dry colorless crystals is obtained. Add acetonitrile to wash and pick out the colorless crystals suitable for X-ray diffraction analysis [(pmib)(TPSP)CuBr] n .
[0012] Furthermore, in step S1, the molar ratio of 2-methylimidazole, potassium hydroxide and α-α'-dichloroparaxylene is 2-3:8-9:1.
[0013] Furthermore, in step S1, the stirring reaction conditions are: room temperature, 1.5h to 2h; the stirring overnight conditions are: room temperature, 10 to 12h.
[0014] Furthermore, in step S2, the volume ratio of distilled water to dichloromethane is 1:1-2.
[0015] Furthermore, in step S3, the temperature inside the refrigerator is -20 to -10°C.
[0016] Furthermore, in step S4, the molar ratio of the ligand pmib, TPSP and CuBr is 0.09-0.11: 0.09-0.11: 0.09-0.11.
[0017] Furthermore, in step S4, the volume ratio of acetonitrile to dichloromethane is 19.8-20.8:19.8-20.8.
[0018] Furthermore, in step S4, the stirring time is 1 minute and the volatilization time is 5 to 6 days.
[0019] The beneficial effects of the present invention are:
[0020] (1) The metal-based blue light material provided by the present invention [(pmib)(TPSP)CuBr] n , X-ray diffraction data show that it crystallizes in the monoclinic C 2 / c space group. In the structure of the complex, the copper atom coordinates with the N and P atoms on the ligand, and pmib acts as a bridging ligand to connect the metal units to form a one-dimensional chain structure.
[0021] (2) The metal-based blue light material provided by the present invention [(pmib)(TPSP)CuBr] n , showing efficient solid-state emission at room temperature, the complex shows a strong emission band centered at 442nm, with a half-maximum width (FWHM) of about 75nm. In the fluorescence emission spectrum, the fluorescence emission of the complex is strongest at an excitation wavelength of 375nm; when the excitation wavelength changes from ultraviolet light to blue light, the complex shows an adjustable emission color; in addition, the emission center of the complex tends to move with increasing temperature, and when the temperature increases from 80K to 420K, the emission center of the complex shows a slight blue shift of about 10nm, and the CIE coordinates are almost unchanged in the temperature range of 80K-380K. This shows that the complex shows a relatively stable fluorescence color with changes in temperature.
[0022] (3) The metal-based blue light material provided by the present invention [(pmib)(TPSP)CuBr] n In the temperature range of 80-280K, the complex exhibits zero thermal quenching and maintains a stable luminescence intensity. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0024] Figure 1 The synthetic route of pmib;
[0025] Figure 2 Metal-based blue light material [(pmib)(TPSP)CuBr] nSynthesis and minimum asymmetric unit structure;
[0026] Figure 3 Metal-based blue light material [(pmib)(TPSP)CuBr] n One-dimensional chain structure; Cu, sky blue; N, blue; C, gray; P, green; Br, dark green; hydrogen atoms are omitted for clarity;
[0027] Figure 4 Metal-based blue light material [(pmib)(TPSP)CuBr] n Powder X-ray diffraction pattern of
[0028] Figure 5 Metal-based blue light material [(pmib)(TPSP)CuBr] n and pmib, infrared spectra of TPSP;
[0029] Figure 6 Metal-based blue light material [(pmib)(TPSP)CuBr] n Thermogravimetric diagram of
[0030] Figure 7 At 298K, the metal-based blue light material [(pmib)(TPSP)CuBr] n Fluorescence excitation and emission spectra (λ em =442nm);
[0031] Figure 8 At 298K, the metal-based blue light material [(pmib)(TPSP)CuBr] n CIE coordinate diagram of
[0032] Fig. 9 Metal-based blue light material [(pmib)(TPSP)CuBr] n The temperature-dependent fluorescence spectrum of
[0033] Fig.10 Metal-based blue light material [(pmib)(TPSP)CuBr] n Temperature-dependent fluorescence emission intensity integral curve;
[0034] Fig.11 Metal-based blue light material [(pmib)(TPSP)CuBr] n Temperature-dependent CIE diagram;
[0035] Fig.12 Metal-based blue light material [(pmib)(TPSP)CuBr] n Photoluminescence quantum efficiency measured at 298K;
[0036] Fig.13 Metal-based blue light material [(pmib)(TPSP)CuBr] n Fluorescence lifetime decay curves at room temperature. DETAILED DESCRIPTION
[0037] It should be mentioned before discussing the exemplary embodiments in more detail that some exemplary embodiments are described as processes or methods depicted as flow charts. Although the flow charts describe the operations as sequential processes, many of the operations therein can be implemented in parallel, concurrently or simultaneously. In addition, the order of the operations can be rearranged. The process can be terminated when its operation is completed, but can also have additional steps not included in the accompanying drawings. The process can correspond to a method, function, procedure, subroutine, subprogram, etc.
[0038] It should be understood that, although the terms "first", "second", etc. may be used herein to describe various units, these units should not be limited by these terms. These terms are used only to distinguish one unit from another unit. For example, without departing from the scope of the exemplary embodiments, the first unit may be referred to as the second unit, and similarly the second unit may be referred to as the first unit. The term "and / or" used herein includes any and all combinations of one or more of the listed associated items.
[0039] The present invention provides a metal-based blue light material, wherein the metal-based blue light material is a complex, wherein the ligand is pmib, wherein the pmib is 1,4-bis(imidazole-1-ylmethyl), and the single crystal structure molecular formula of the metal-based blue light material is: [(pmib)(TPSP)CuBr] n The metal-based blue light material belongs to the monoclinic system, the space group is C 2 / c, and the crystal parameters are α=90°, β=116.252(3)°, γ=90°, Z=8, The minimum asymmetric unit structure center of the metal-based blue light material is composed of a crystallographically independent Cu and a Br atom to form a classic [CuBr] coordination mode, which is extended outward through the connection between the Cu atom and the ligands pmib and TPSP to form a one-dimensional chain structure.
[0040] The present invention provides a method for preparing a metal-based blue light material, the method comprising:
[0041] S1. Dissolve 2-methylimidazole and potassium hydroxide in dimethyl sulfoxide, stir to react, add α-α'-dichloro-p-xylene, and stir overnight to obtain a reaction solution;
[0042] S2. The reaction solution in the previous step was broken with distilled water, and then liquid-liquid extraction was performed with dichloromethane, and the layers were separated to obtain an organic layer, which was dried over anhydrous magnesium sulfate, filtered and concentrated;
[0043] S3. Add ether to the concentrate from the previous step, place in a refrigerator overnight, crystallize, and filter to obtain the ligand pmib;
[0044] S4. Add CuBr, pmib, TPSP, acetonitrile and dichloromethane into a beaker and stir. Filter the mixture after stirring and pour it into a clean beaker. Seal it with plastic wrap and pierce it. Volatilize it at room temperature. After the solvent evaporates, a mixture containing dry colorless crystals is obtained. Add acetonitrile to wash and pick out the colorless crystals suitable for X-ray diffraction analysis [(pmib)(TPSP)CuBr] n .
[0045] The reagents involved in the experiment were from manufacturers such as Anage Chemical, Alfa Reagent and Sinopharm Group, and the details are shown in Table 1; the reagents involved were used directly without further purification.
[0046] Table 1 Reagents:
[0047]
[0048] The equipment and instruments used in the experiment are shown in Table 2:
[0049]
[0050] Example 1
[0051] Preparation of PMIB (ref. Figure 1 shown):
[0052] S1. Dissolve 2-methylimidazole (0.82 g, 10 mmol) and potassium hydroxide (2.30 g, 41 mmol) in dimethyl sulfoxide (15 ml), and then stir the reaction mixture for 2 hours. Add α-α'-dichloro-p-xylene (0.88 g, 5 mmol) to the reaction mixture, and continue stirring the reaction for 12 hours.
[0053] S2. After the reaction, add 150 ml of distilled water to the flask and perform liquid-liquid extraction with dichloromethane (150 ml). Separate the liquids, take the organic layer, add anhydrous magnesium sulfate (5 g, 41.5 mmol), stir for 2 hours, filter and evaporate until 10 ml of liquid remains.
[0054] S3. Add 200 ml of ether to the above 10 ml of liquid and place it in the freezer (-20°C to -10°C) overnight to allow the product to precipitate. The final product is a yellow powder.
[0055] Metal-based blue light material [(pmib)(TPSP)CuBr] n Preparation:
[0056] S4. Add CuBr (14.3 mg, 0.1 mmol), pmib (26.6 mg, 0.1 mmol), TPSP (30 mg, 0.1 mmol), acetonitrile (20 mL) and dichloromethane (20 mL) into the flask, stir for 1 minute, filter the resulting mixture and pour it into a clean beaker with a volume of 100 mL, seal it with plastic wrap and poke 5 holes, and evaporate it in a dry and cool environment at room temperature for 6 days. After the solvent evaporates, a dry colorless crystal and a precipitate mixture are obtained, and 50 ml of acetonitrile is added to wash and pick out the colorless crystals [(pmib)(TPSP)CuBr] suitable for X-ray diffraction analysis. n .
[0057] Data collection, data reduction and unit optimization were performed using two program packages, Luker Instrument Service v4.2.2 and SAINT V8.34 A. The complex structure was solved using the SHELXS program package, and the crystal data were optimized using the full matrix least squares method using the SHELXL program package. Absorption correction was performed using the multi-scan program package SADABS. The hydrogen atoms of the organic ligands were analyzed using the riding mode on the SHELXTL program package. 2 The crystallographic data of the complex are shown in Table 3. The bond lengths of some of the complexes are The data of bond angle (°) are shown in Table 4.
[0058] Table 3 Crystallographic parameters of the complexes:
[0059]
[0060]
[0061] a R1=Σ(||F0|-|Fc||) / Σ|F0|; b wR2=[Σw(|F0 2 |-|Fc 2 |) 2 / Σw|F0 2 | 2 ] 1 / 2 ; c GOF=[∑[w(F0 2 -Fc 2 ) 2 ] / (Nobs-Nparams)] 1 / 2 ,
[0062] Based on the data I>2σ(I).
[0063] Table 4 Important bond lengths in the complex crystal structure and bond angles():
[0064]
[0065]
[0066] Powder X-ray diffraction analysis: Figure 4 As shown in the figure, the red spectrum is drawn from experimental data, and the black spectrum is obtained by computer simulation based on the crystal structure. From this figure, it can be seen that the experimental value and the simulation value of the complex can match very well, indicating that the complex is pure phase.
[0067] Infrared spectrum: IR (KBr pellet, cm -1 :):1502(s),1414(w).1393(w),1272(m),1240(m),1188(m),1089(s),805(s),665(m),626(w),781(m),523(s). like Figure 5 As shown, the black spectrum is drawn from the data obtained from the crystal, and the red and blue spectrum are drawn from the data obtained from the ligand. It can be seen from the figure that the vibration contraction peaks of the ligand and the complex are almost the same, indicating the presence of organic ligands in the complex.
[0068] Elemental analysis method: Theoretical value of elemental analysis (%) (C 31 H 33 CuBrN3P): C, 37.4; H, 3.3; N, 4.2; P, 11.1 Experimen tal value: C, 37.6; H, 3.4; N, 4.2; P, 11.5.
[0069] Thermogravimetric analysis: Figure 6 As shown, the thermal stability of the complex from room temperature to 800 ° C was studied. From the TGA curve, it can be seen that the complex exhibits good thermal stability, and its mass loss is divided into two steps. The first weight loss of the complex is about 62-63% observed between 100-422 ° C due to the removal of halogen and part of the ligand. The second weight loss between 422-800 ° C can be attributed to the complete removal of the remaining ligand.
[0070] Fluorescence test: Figure 7 As shown, the complex exhibits a strong emission band centered at 442 nm, with a full width at half maximum (FWHM) of about 75 nm and CIE coordinates of (0.2055, 0.1627) ( Figure 8 ), showing dark blue light. Fig.13As shown, the PL lifetime is 8.35 μs. In addition, the complex exhibits excitation band coverage from deep UV light. Figure 7 As shown in Table 5, in the fluorescence emission spectrum, the fluorescence emission of the complex is strongest at an excitation wavelength of 382 nm. As shown in Table 5, the photoluminescence quantum yield (PLQY) of the complex in the solid state is 41.05%, and the fluorescence decay rate (k r )(k r =Φ PL τ -1 ) is 3.29×10 4 s -1 Considering Φ PL =k r / (k r +k nr ), where k nr is the rate of the nonradiative process including nonradiative singlet decay and ISC, k of the complex nr The value is estimated to be 8.68×10 4 s -1 .
[0071] Table 5 Solid-state photophysical data of the complex at room temperature:
[0072]
[0073] a Radiative rate constant calculated k r =Φ / τ. b Nonradiative rateconstant calculated k nr r=(1-Φ) / τ.
[0075] Fluorescence quenching property study: This invention studies the dependence of fluorescence on temperature, such as Fig. 9 and Fig.10 As shown in the figure, as the temperature gradually increases from 80K to 420K, the emission center of the complex shows a slight blue shift of about 10nm and a significant zero-thermal quenching phenomenon occurs in the temperature range of 80K-280K. The results show that as the temperature changes, the complex exhibits a relatively stable fluorescence color. Fig.11 As shown in the figure, as the temperature increases, the luminescence of the complex changes from dark blue at low temperature (80K) to blue at high temperature (420K). Correspondingly, the CIE coordinates change from (0.1852, 0.171) at 80K to (0.2123, 0.2285) at 420K. In the range of 80-380K, the CIE coordinates hardly change, indicating the stability of the luminescence color.
[0076] Photoluminescence quantum efficiency and fluorescence lifetime: The quantum efficiency curve of photoluminescence is as follows: Fig.12 As shown in Figure 2, at 298K, the photoluminescence quantum yield (PLQY) of the solid complex is 27.53%. The photoluminescence fluorescence lifetime curve is shown in Figure 2. Fig.13 As shown, at 298K, the fluorescence lifetime of the complex is 8.35μs.
[0077] The above is only an embodiment of the present invention. The common sense such as the known specific structure and characteristics in the scheme is not described in detail here. The ordinary technicians in the relevant field know all the common technical knowledge in the technical field of the invention before the application date or priority date, can know all the existing technologies in the field, and have the ability to apply the conventional experimental means before that date. The ordinary technicians in the relevant field can improve and implement this scheme in combination with their own abilities under the enlightenment given by this application. Some typical known structures or known methods should not become obstacles for ordinary technicians in the relevant field to implement this application. It should be pointed out that for those skilled in the art, without departing from the structure of the present invention, several deformations and improvements can be made, which should also be regarded as the scope of protection of the present invention, which will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.
Claims
1. A metal-based blue light material, characterized in that: The metal-based blue light material is a complex, the ligand is pmib, the pmib is 1,4-bis(imidazole-1-ylmethyl), and the single crystal structure molecular formula of the metal-based blue light material is: [(pmib)(TPSP)CuBr] n The metal-based blue light material belongs to the monoclinic system, the space group is C 2 / c, and the crystal parameters are α=90°, β=116.252(3)°, γ=90°, Z=8, 2. The metal-based blue light material according to claim 1, characterized in that: The minimum asymmetric unit structure center of the metal-based blue light material is composed of a crystallographically independent Cu and a Br atom to form a classic [CuBr] coordination mode, which is extended outward through the connection between the Cu atom and the ligands pmib and TPSP to form a one-dimensional chain structure.
3. A method for preparing a metal-based blue light material as claimed in claim 1 or 2, characterized in that: The reaction comprises the following steps, S1: Dissolve 2-methylimidazole and potassium hydroxide in dimethyl sulfoxide, stir to react, add α-α'-dichloro-p-xylene, and stir overnight to obtain a reaction solution; S2: The reaction solution in the previous step was dehydrated with distilled water, and then liquid-liquid extraction was performed with dichloromethane. The layers were separated to obtain an organic layer, which was dried with anhydrous magnesium sulfate, filtered and concentrated; S3: Add ether to the concentrate from the previous step, place in a refrigerator overnight, crystallize, and filter to obtain the ligand pmib; S4 Add CuBr, pmib, TPSP, acetonitrile and dichloromethane into a beaker and stir. Filter the mixture after stirring and pour it into a clean beaker. Seal it with plastic wrap and pierce it. Volatilize it at room temperature. After the solvent evaporates, a mixture containing dry colorless crystals is obtained. Add acetonitrile to wash and pick out the colorless crystals suitable for X-ray diffraction analysis [(pmib)(TPSP)CuBr] n .
4. The method for preparing a metal-based blue light material according to claim 3, characterized in that: In the step S1, the molar ratio of 2-methylimidazole, potassium hydroxide and α-α'-dichloroparaxylene is 2-3:8-9:
1.
5. The method for preparing a metal-based blue light material according to claim 3, characterized in that: In the step S1, the stirring reaction conditions are: room temperature, 1.5 hours to 2 hours; the stirring overnight conditions are: room temperature, 10 to 12 hours.
6. The method for preparing a metal-based blue light material according to claim 3, characterized in that: In step S2, the volume ratio of distilled water to dichloromethane is 1:1-2.
7. The method for preparing a metal-based blue light material according to claim 3, characterized in that: In step S3, the temperature inside the refrigerator is -20 to -10°C.
8. The method for preparing a metal-based blue light material according to claim 3, characterized in that: In the step S4, the molar ratio of the ligand pmib, TPSP and CuBr is 0.09-0.11: 0.09-0.11: 0.09-0.
11.
9. The method for preparing the metal-based blue light material according to claim 3, characterized in that: In the step S4, the volume ratio of acetonitrile to dichloromethane is 1:1-2.
10. The method for preparing a metal-based blue light material according to claim 3, characterized in that: In step S4, the stirring time is 1 minute and the volatilization time is 5 to 6 days.
Citation Information
Patent Citations
Carbon compound reduction catalyst
JP2022124864A